Diminished ovarian reserve may not be associated with a poorer fresh cycle outcome in women < 38 years - Huizi Jin; Enqi Yan; Dan Chen; Mengya Zhao; Wenju Peng; Yaxin Guo; Lei Jin (BMC, 2023)
Abstract Background Previous studies have discussed the pregnancy outcomes of diminished ovarian reserve (DOR) patients. However, data on embryonic development potential, neonatal outcomes, and maternal complications of DOR patients still remained unknown. This is the first study to investigate the risk of DOR on pregnancy and perinatal outcomes among women < 38 years. Methods Retrospective cohort study was conducted. Patients (< 38 years of age) undergoing their first oocyte retrieval cycle were included. Patients were divided into DOR group and non-DOR group. Pregnancy outcomes of fresh cycle and cumulative live birth rate and perinatal outcomes after one oocyte retrieved cycle were compared between DOR and non-DOR group. Result(s) From January 2016 to September 2020, there were 8,179 patients involved: 443 patients in the DOR group and 7,736 patients in the non-DOR group. The incidences of live birth and clinical pregnancy did not differ significantly between patients with or without DOR after fresh cycle transfer, but the cumulative live birth rate was significantly lower in DOR group. Among women who had singleton live births, after binary logistic regression, the rates of maternal complications and neonatal outcomes were comparable in the two groups. Conclusion(s) DOR patients (< 38 years of age) showed similar pregnancy outcomes in the first fresh embryo transfer cycle but a lower chance of live birth after a whole oocyte retrieval cycle to non-DOR patients and DOR is not associated with adverse perinatal outcomes.